Effects of phosphodiesterase (III/IV)-inhibitors and cytokines on mechanical properties of neutrophilic granulocytes in neonates and adults - Ruef, Peter; Craciun, Eugenia Maria; Altfelder, Jan Felix; Simon, Christoph; Frommhold, David; Koch, Lisa; Pöschl, Johannes (Clinical hemorheology and microcirculation, 2010)
Sequestration of activated PMN and enrichment in tissues play a key role in tissue damage during septicaemia and after ischemia/reperfusion. Since polymorphonuclear neutrophilic granulocytes (PMN) of term neonates show various functional differences